Clear cell meningioma with PEC-oma characteristics. Immunohistochemical and ultrastructural study of a case - Cuccurullo, Luigi; Ferraraccio, Franca; Parlato, Ciro; Accardo, Maria (European Journal of Oncology and Environmental Health, 2008)
Aim. The Authors deem it opportune to report a  case of clear cell meningioma with the morphological, immunohistochemical and ultrastructural features of a perivascular epithelioid cell tumour (PEC-oma). The interest in this finding is due not only to the low frequency of clear cell meningiomas, but above all to the fact that it presents nodular aspects with a concentric arrangement of the cells around a vessel and with positivity for smooth muscle actin and for the melanogenic antigen HMB-45. Materials and methods. Multiple fragments of this tumour underwent histological, immunohistochemical and electron microscopy investigation. Results. The morphological results showed nodules with a presence in peri-vascular location of mediumsized ovoid elements with a large clear cytoplasm and, along the periphery, of spindle-shaped elements with a dense cytoplasm. These histopathological findings were confirmed ultrastructurally; this technique showed, in the cytoplasmic matrix, intermediate filaments, varying amounts of organules, junctions, and real and virtual intercellular spaces. The immunohistochemical investigation showed high positivity for vimentin, positivity in 60% of the cells for the HMB-45 antigen, and positivity in 40% of the cell population for the smooth muscle actin. Conclusions. The application of complementary morphological techniques showed features that go beyond those of clear cell meningioma and are indicative of a PEC-oma. In applying this diagnosis the Authors appreciate the necessity for caution in the presentation of this finding because it is a single case with objective diagnostic difficulty and because of the numerous current interrogatives surrounding PEC-omas.